2013
DOI: 10.1089/chi.2012.0111
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Obesity Prevention: Fathers' Reflections with Healthcare Providers

Abstract: Background: To prevent childhood obesity, parents and their children's healthcare providers need to engage in effective dialogue. We know much about mothers' experiences, but very little about fathers' experiences.Methods: We explored African-American, Caucasian, and Latino fathers' perceptions and experiences communicating with their children's provider during clinic visits regarding weight, diet, and physical activity. Focus groups (n = 3), grouped by race/ethnicity, including a total of 24 fathers, were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 36 publications
1
24
0
Order By: Relevance
“…The literature was consistent that all HCPs (especially nurses and physicians) have a responsibility to address the topic of obesity with children and their families, as they would with any other health condition, with many of the recommendations drawn from the lived experience literature . Two articles in particular proposed that weight‐related topics are best raised by a HCP with a long‐term, trusting relationship and knowledge of the family , which was also endorsed by an obesity guideline article . Focusing upon practical strategies, two papers recommended that nurses assessing children's weight should highlight any concerns so that physicians can address them when they see children and their families .…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…The literature was consistent that all HCPs (especially nurses and physicians) have a responsibility to address the topic of obesity with children and their families, as they would with any other health condition, with many of the recommendations drawn from the lived experience literature . Two articles in particular proposed that weight‐related topics are best raised by a HCP with a long‐term, trusting relationship and knowledge of the family , which was also endorsed by an obesity guideline article . Focusing upon practical strategies, two papers recommended that nurses assessing children's weight should highlight any concerns so that physicians can address them when they see children and their families .…”
Section: Resultsmentioning
confidence: 80%
“…All three categories of studies recommended that HCPs should initiate weight‐related discussions as early as possible in order to prevent obesity , although there was divergent information in the lived experience articles around the context within which the topic could be raised. For example, one study suggested that the topic should be raised at all well‐child visits, whether or not a weight issue had been identified ; another article suggested that HCPs should discuss weight in the context of a clearly associated health problem (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These relationships are important because a recent qualitative study found that fathers who are involved in their child's health care are open to advice regarding their child's weight, diet, and physical activity, although these fathers often felt left out or completely ignored by the physician. 14 If fathers are open to advice, but are not receiving it, practitioners may be missing key opportunities regarding diet, physical activity, or weight management, and thus child obesity prevention.…”
Section: Discussionmentioning
confidence: 99%
“…In a sample of EHS staff, a tendency to stereotype men into traditional gender roles (e.g., disinterested in activities with their child, not wanting to talk about emotional matters) contributed to difficulty implementing an approach to father involvement that emphasized individualized interactions between staff and fathers . Collectively, these factors are experienced by fathers as a lack of respect, and they reinforce traditional cultural norms of the predominant role of mothers as primary caregivers in the first 1,000 days , which in turn have implications for fathers’ attendance at appointments and receptivity to the information provided .…”
Section: Barriers To Father Engagementmentioning
confidence: 97%